Discourses and Environmental Controversies in the Footprints of Transhumant Livestock: A Comparative Gaze Between Patagonia Argentina and Italy - Bindi, Letizia (2024)
This paper reviews the current challenges of extensive and transhumant grazing, by comparing European and American processes. In the first case, Italian Molise’s experiences are analyzed, in the second case from North Argentine Patagonia. It investigates the footprints of passing cattle, searching the double recognition made by institutions and populations. It seeks to understand the strands that link the meanings of practices, addressing the socio-environmental challenges of territories between marginal and essentialized, which refer to structural aspects, customs and specific practices. The cases are compared by understanding them within the Anthropocene. To make visible their crossing tensions, it appeals to the Capitalocene critical theories, which associate sustainable development, dissemination and education with a new discourse on global heritage. From here, and in the light of experiences, relationships between intangible cultural heritage and sustainable development around livestock farming are made explicit, based on the shared difficulties in recognizing the activity outside of an essentializing perspective.